Diskursus Kritis Nenengisme: Resistensi Perempuan Petani terhadap Ideologi melalui Media Sosial - Ahmad Ridwan; Muhammad Faruki; Achmad Rizal Affandi (Universitas Negeri Surabaya, 2025)
This study investigates the symbolic resistance of peasant women to dominant agrarian ideologies through discursive practices on social media, with a case study of Facebook user Neneng Rosdiyana. Stemming from structural inequality in Indonesia’s agrarian system and the marginalization of rural women, the research examines how everyday language infused with humor, critique, and local idioms is used to construct resistance discourse. The study employed a qualitative case study design with netnographic observation, analyzing Facebook posts and a YouTube report collected between March and April 2025. The data were analyzed using a Critical Discourse Analysis (CDA) approach with Fairclough’s three-dimensional framework: textual description, interpretation of discursive practice, and explanation of discourse within broader social structures. The findings reveal that Neneng’s practices are not merely expressive but constitute ideological articulations challenging masculinist, academic, and state-centered agrarian narratives. Symbols such as the hoe, collective labor, and vernacular expressions function as tools of resistance against patriarchy and capitalism. Her collective practices represent a model of practical feminism rooted in solidarity rather than state intervention. This research highlights the novelty of recognizing women peasants as discursive agents in digital arenas, expanding debates on agrarian feminism and everyday resistance in rural Indonesia.